Beginner's Guide to Visual Analysis of Perovskite and Organic Solar Cell Current Density–Voltage Characteristics - These, Albert; Koster, L. Jan Anton; Brabec, Christoph; Le Corre, Vincent Marc (Advanced Energy Materials, 2024)
The current density–voltage characteristic (J–V) is a critical tool for understanding the behavior of solar cells. This study presents an overview of the key aspects of J–V analysis and introduces a user-friendly flowchart that facilitates the swift identification of the most probable limiting process in a solar cell, based mainly on the outcomes of light-intensity-dependent J–V measurements. The flowchart is developed through extensive drift-diffusion simulations and a rigorous review of the literature, with a specific focus on perovskite and organic solar cells. Moreover, the flowchart proposes supplementary experiments that can be conducted to obtain a more precise prediction of the primary performance losses. It therefore serves as an optimal starting point to analyse performance losses of solar cells.
CRIS-Team Scopus Importer:2024-04-19
Keywords: current-voltage characteristic; drift-diffusion simulation; organic solar cell; perovskite solar cell; photovoltaics